The Role of Perception of Organizational Support, Organizational Culture, and Intention to Stay on the Affective Commitment of Employees at CV. Media Pratama Solusinet in Tegal - Tinawati Setiawan; Setyowati Subroto; Ira Maya Hapsari (LP2M IAIN Palopo, 2026)
This study aims to analyze affective commitment and the factors influencing it, namely perceived organizational support, organizational culture, and intention to stay, in relation to affective commitment. The research methodology employs both quantitative and qualitative approaches. The population and sample of this study consist of 40 employees of CV Media Pratama Solusinet in Tegal City. The data used are primary data collected via a questionnaire administered to respondents, containing statements rated on a Likert scale from 1 to 5. The data were then processed and analyzed using classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination test). The results of the t-test for the variable Perception of Organizational Support on Affective Commitment yielded a significance value of 0.000 < 0.05, meaning H1 is accepted; the variable “Organizational Culture” on “Affective Commitment” yielded a significance value of 0.085 > 0.05, meaning H2 is rejected; the variable “Intention to Stay” on “Affective Commitment” yielded a significance value of 0.515 > 0.05, meaning H3 is rejected. The F-test yielded a significance value of 0.00 < 0.05. This indicates that the variables Perception of Organizational Support, Organizational Culture, and Intention to Stay collectively or simultaneously have a significant effect on Affective Commitment. The F-test result is supported by the coefficient of determination, showing that these three variables contribute 94.5% to Affective Commitment.